Variability of blood pressure, pulse pressure, and mean arterial pressure in hypertensive individuals - Berek, Pius Almindu Leki; Amaral, Fransiska; Akoit, Handrianus; Nahak, Maria Paula Marla; Mau, Djulianus Tes; Fouk, Maria Fatimah Wilhelmina Abuk; Made, Yovita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Hypertension is a major risk factor for cardiovascular disease and remains a public health issue, particularly in areas with limited access to healthcare services, such as the Indonesia–Timor Leste border region. Blood pressure variability, pulse pressure (PP), and mean arterial pressure (MAP) are important indicators for assessing the risks of long-term complications. Purpose: To determine the profile and variability of blood pressure, PP, and MAP among hypertensive individuals, as well as the relationship between sociodemographic characteristics and these parameters. Method: A quantitative descriptive design with a cross-sectional approach was employed. Data were collected from 124 respondents through blood pressure measurements taken at three different time points. Mean systolic and diastolic blood pressure (SBP and DBP), PP, and MAP were analyzed, along with comparisons between measurement times and respondent characteristics. Result: The mean systolic blood pressure (SBP) was 151.27 mmHg, and the mean diastolic blood pressure (DBP) was 89.86 mmHg, indicating that most participants fell into hypertension grade 1–2 categories. The mean PP was 61.43 mmHg and MAP was 110.32 mmHg, both exceeding normal thresholds, suggesting potential vascular complications. Significant fluctuations were found in SBP and PP between the second and third measurements (p=0.014 and p=0.032, respectively), while DBP and MAP remained relatively stable. No significant associations were found between sex, education level, or occupation with the blood pressure parameters. Conclusion: Blood pressure was relatively high and tended to be stable between measurements, with significant variability in systolic and pulse pressures (p<0.05). Meanwhile, sociodemographic characteristics such as age, gender, education, and occupation did not show a significant association with blood pressure, PP, or MAP. Suggestion: Hypertension control programs need to focus on an individualized approach with routine blood pressure monitoring using HBPM, stabilizing blood pressure variability, and improving patient education. Programs must also be tailored to sociocultural conditions and supported by simple digital technology for early detection in border communities.